Effect of Water Stress and Antitranspirants on the Chlorophyll Contents of the Leaves of Pongamia pinnata (L.) Pierre - Nautiyal, S.; Negi, D. S.; Kumar, Shiv (Indian Forester, 1996)
The effect of water stress and some antitranspirants on the chlorophyll contents of the leaves of Pongamia pinnata (L) Pierre, were studied uuder controlled laboratory conditions. The chlorophyll a, b and total, invariably increased from daily to fortnightly watering interval, however there is a sharp decrease in case of monthly watering interval. The chlorophyll a, b, ratio was maximum at weekly watering interval minimum at monthly watering interval. It shows that the mild trees effects the formation/ accumulation of chlorophyll b more than chlorophyll a (weekly watering interval) however, heavy stress destroy both chlorophyll a and b with the result less photosynthesis and low growth (monthly watering interval).